Biodegradable mesoporous calcium–magnesium silicate-polybutylene succinate scaffolds for osseous tissue engineering - Zhang X (Dove Medical Press, 2015)
Xinxin Zhang,1,2,* Chi Zhang,3,* Wei Xu,1,* Biao Zhong,3 Feng Lin,3 Jian Zhang,3 Quanxiang Wang,4 Jiajin Ji,4 Jie Wei,4 Yang Zhang1 1TongRen Hospital, School of Medicine, Shanghai Jiao Tong University, 2Shanghai Institute of Materia Medica, Chinese Academy of Sciences, 3Shanghai Sixth People’s Hospital, Shanghai Jiao Tong University, 4Key Laboratory for Ultrafine Materials of Ministry of Education, East China University of Science and Technology, Shanghai, People’s Republic of China *These authors contributed equally to this work Abstract: The structural features of bone engineering scaffolds are expected to exhibit osteoinductive behavior and promote cell adhesion, proliferation, and differentiation. In the present study, we employed synthesized ordered mesoporous calcium–magnesium silicate (om-CMS) and polybutylene succinate (PBSu) to develop a novel scaffold with potential applications in osseous tissue engineering. The characteristics, in vitro bioactivity of om-CMS/PBSu scaffold, as well as the cellular responses of MC3T3-E1 cells to the composite were investigated. Our results showed that the om-CMS/PBSu scaffold possesses a large surface area and highly ordered channel pores, resulting in improved degradation and biocompatibility compared to the PBSu scaffold. Moreover, the om-CMS/PBSu scaffold exhibited significantly higher bioactivity and induced apatite formation on its surface after immersion in the simulated body fluid. In addition, the om-CMS/PBSu scaffold provided a high surface area for cell attachment and released Ca, Mg, and Si ions to stimulate osteoblast proliferation. The unique surface characteristics and higher biological efficacy of the om-CMS/PBSu scaffold suggest that it has great potential for being developed into a system that can be employed in osseous tissue engineering. Keywords: bone repair, polybutylene succinate, calcium–magnesium silicate, ordered mesoporous, proliferation